Assessing Causality Between Plasma Brain‐Derived Neurotrophic Factor With Major Depression Disorder: A Bidirectional Mendelian Randomization Study - Ming Chen; Hao‐Zhang Huang; Yi‐Hui Liu; Qiang Li; Lin‐Yan Fu; Cai‐Lan Hou (Brain and Behavior)
ABSTRACT Purpose This study employed a two‐sample Mendelian randomization (MR) approach to investigate the bidirectional relationship between brain‐derived neurotrophic factor (BDNF) and major depressive disorder (MDD), addressing gaps left by prior observational studies. Methods We utilized Genome‐Wide Association Study (GWAS) datasets, including MDD information from the Psychiatric Genomics Consortium (PGC) and the UK Biobank (N = 500,199), along with plasma BDNF measurements from the FinnGen Consortium (N = 619). In a subsequent phase, we analyzed MDD data from FinnGen (N = 448,069) with plasma BDNF data from three additional GWAS sources: UK Biobank (N = 33,924), deCODE (N = 35,353), and INTERVAL (N = 3301). Multiple MR methods were applied to ensure a robust analysis. Results The inverse variance weighted (IVW) method revealed no significant association between plasma BDNF levels and the risk of developing MDD (IVW odds ratio [OR] = 1.00, 95% confidence interval [CI] = 0.99–1.01, p = 0.769). Similarly, no causal effect of the BDNF gene on MDD was identified (OR = 0.91, CI = 0.23–3.56, p = 0.893). Furthermore, there was no evidence supporting a causal link between MDD and plasma BDNF levels (OR = 0.99, CI = 0.89–1.09, p = 0.783). The second phase of analysis confirmed the absence of bidirectional causal relationships. Conclusion This bidirectional MR analysis provides no evidence of a causal association between plasma BDNF levels and MDD. These findings prompt a re‐evaluation of plasma BDNF as a biomarker for MDD and emphasize the need for further investigation into its functional role within the plasma as well as its levels and activity in the brain and cerebrospinal fluid.